Comment on the paper “Analysis of reasons for organ donor shortage and the main directions of its overcoming” - M. Sh. Khubutia; M. G. Minina (Трансплантология (Москва))
Comment on the paper “Analysis of reasons for organ donor shortage and the main directions of its overcoming”.